Assessment of Potentially Inappropriate Medication (PIMs) in Older Adult Patients at the Geriatric Polyclinic of a General Hospital in Central Java - Cholisoh, Zakky; Riswanto, Muhammad Imam (Jurnal Ilmu Kesehatan, 2023)
One of the most critical issues affecting older adults is the increasing use of potentially inappropriate medication (PIMs). The use of PIMs is associated with drug-related problems, as well as undesirable drug effects. This study aimed to assess the prevalence of potentially inappropriate medication and the most commonly prescribed PIMs category in older adults. This research method is observational with a cross-sectional design. Drugs were analyzed using the 2019 Beers criteria compiled by The American Geriatrics Society (AGS), classifying PIMs into five categories. The inclusion criteria in this study were patients aged ≥65 years, using at least one drug, with a duration of drug use of at least one month, and analyzing this research data descriptively. The results showed that out of 134 prescriptions consisting of 773 drug items, 95 drug items were potentially inappropriate for use in older adults. The prevalence of PIMs was 12%, and if classified by category, then partly in order, inappropriate medication included category 1 (8.2%); category 2 (0.6%); category 3 (2.8%); category 4 (0.3%); category 5 (0.1%). The most common drugs included in category 1 PIMs criteria were proton pump inhibitors (PPIs), namely lansoprazole and omeprazole. Conclusion: In this study, the prevalence of potentially inappropriate Medication in older adults was 95 drug items (12%), and the more commonly prescribed category of PIMs is category one drugs and should avoid category one drugs in older adults.